Reactions of 1-p-Dimethylaminobenzyl-2-p-Dimethylaminophenylbenzimidazole with Cobalt(II), Zinc(II) and Cadmium(II) Salts - Mallesh, H.B.; Krishnamurthy, G.; Shashikala, N. (Asian Journal of Chemistry, 2016)
Synthesis of 1-p-dimethylaminobenzyl-2-p-dimethylaminophenylbenzimidazole (dmabdmapb, L) and its complexes of cobalt(II), [CoX2L2]·nH2O (X = Cl, n = 3; X = Br, n = 0), Col2L2(OH2), zinc(II) and cadmium(II), MX2L2·nH2O (M = Zn, X = Cl, n = 0; X = Br, n = 3; X = I, n = 1; M = Cd, X = Cl, Br, I), [ZnL(OH2)3](ClO4)2·3H2O and [CdL1.5(OH2)2)2](ClO4)4 is described. They have been characterized by IR, UV-visible and 1H NMR spectra and magnetic susceptibility measurements. The electronic and magnetic susceptibility studies suggest a tetrahedral geometry for CoX2L2 (X = Cl, Br), zinc(II) and cadmium(II) complexes and a trigonal bipyramidal geometry for CoI2L2(OH2).